SURVEI PEMBINAAN USIA DINI PENGCAB PSSI KOTA MADIUN - ILVAN GILIS, NOSA Ilvan (Jurnal Prestasi Olahraga, 2013)
Football is the most popular sport over the world, whole society very like this sport. Recently, football already have rapid development. On Indonesia, football have priority on its existence, its proved by the existence of football league namely Indoensian league or commonly said IPL (Indonesia Premier League). On East Java, especially on grassroots development that located on Madiun city, Indonesian Football Association of Madiun city still not good enough on grassroots development, it proved from the lack of player regeneration from old player to new player that more potential, from coaching knowledge on the its system, for infrastructure fulfillment to grassroots development and support from parties that concerned on football development specially football. Based on the result of research that obtained data from the grassroots development of Indonesian Football Association of Madiun city Grassroots development of the development of grassroots player and coach development to grassroots still not good enough, since there is a ineffective coaching system and support from Indonesian Football Association of Madiun city to observe coachig system that done to grassroots development and due to the lack of coaching lisence provision and the renewing of coaching knowledge that carried out by Indonesian Football Association of Madiun city and the lack of coach to knowing new coaching knowledge. There is an organization system having formation of management sturucture and financial for management formation, for management structure on Indonesian Football Association of Madiun city still not good enough, lack of comunication, knowledge  concerning grassroots developments that lack, and the existence of parties that give priority to personal interest and do not support, it proved from there is no observation and they also do not know the tasks on management and the lack of movement space in execute their job. On soccer scholl management is already good, it proved the board execute their job based on their tasks and find ideas in overcome problems within soccer school that they develop. Budgeting system for soccer school at Madiun city still not good, there is no assisstance from football assocation is the cause of cumberer in execute a development on soccer school. Within soccer school funding it already said that good enough, since soccer school become more independent in finding a donation and able to close their fund shortage on development program. The condition of infrastructure within soccer school still not good enough, due of fund constraint to execute needs fulfillment of grassroots development. Keywords : Indonesian Football Association of Madiun city grassroots development.